Perkembangan karakter pada anak usia dini - Sholihah, Nur Hidayatus (Maliki Interdisciplinary Journal, 2024)
Early childhood is the first step in the moral formation of children. Instill good values ​​in children so that they grow into human beings with character. Each child has its own characteristics. Children have unique characters, are active, curious, and imaginative. They like to fight and enjoy new things, so they thrive with the guidance of affection from their parents and the environment around them. The word character comes from the Greek word charassein which means to sculpt to form patterns. Noble traits are not owned by every human being from birth, however, extensive nurturing and schooling are required. Physical growth, personal maturation, and interpersonal maturation are all facets of human development. Honesty, discipline, tolerance, hard effort, independence, curiosity, social care, environmental care, responsibility, and a desire for peace should be among the many character characteristics fostered in children from an early age. Issues with moral formation in young children; media’s pernicious effects; teen sexual activity; smartphone addiction. Teachers, principals, and even school boards can help foster healthy growth in young children by modeling positive behavior. Indicators of character development training for everyday actions. This will set the stage for the child’s character and overall surroundings to flourish. The environment is considered an important part of the learning process in character development.